Involuntary confinement during the COVID -19 Pandemic: Mental and psychosocial health costs - Castellanos Suárez, Viviana (Horizonte Sanitario, 2023)
Objective: To identify the costs of involuntary confinement due to the COVID -19 pandemic in the mental and psychosocial health.Materials and methods: An exploratory documentary review of involuntary confinement and its costs in the human nature was carried out. Four descriptors and their combinations, mental health, health psychosocial, costs in the COVID -19 pandemic, and involuntary confinement were searched in bibliographic databases and online in journals and public organizations from 2019 to 2021. 20 studies were found. After selecting and analyzing the documentation five studies were excluded as they were not relevant. To analyze the data, the information was classified in mental health costs, identifying neurophysiological effects such as confusion in the fight-flight system and hyperactivation and/or hypoactivation of the nervous system, and in psychosocial costs in the face of confinement, such as the feeling of anticipated and continuous threat, anxiety, fear, sadness, pain, depression, over stress, trauma, vulnerability, and cultural changes.Results: The COVID-19 pandemic is unprecedented, historical, multinational and has a multidimensional impact. The lack of mitigation and the time exceeded resisting it has exposed the humans to continuous stressors that undermine confidence and cause uncertainty. In addition, during the pandemic, confinement brought with it high mental health costs of a neurological and psychosocial nature, such as overstress, anxious-depressive symptoms, vulnerability in personal and social integrity.Conclusions: It is necessary to generate emotional well-being strategies to reduce the impact on mental and psychic health and the social fabric by promoting the recovery of networks of empathy, benevolence, compassion, solidarity support, collectivizing pain and losses, thus recovering confidence and security in oneself and in others.